Habitat preferences of ptarmigan hunters in Norway - Kaltenborn, Bjørn P.; Andersen, Oddgeir (European journal of wildlife research, 2009)
Hunting for willow ptarmigan ( Lagopus lagopus ) is a popular recreational activity in Norway, but studies of the hunters are limited. While large game management in Norway is based on sound models and research, management of small game hunters and hunting have not been subject to the same rigour. Compared to the extensive body of knowledge about ptarmigan behaviour and habitat preferences, the knowledge base on ptarmigan hunters is very limited. We surveyed the habitat preferences of 3,056 hunters to identify preferred landscape categories using pictures covering a range of landscape types. We also examined to which extent residence types and forms of hunting were related to habitat preferences. Through factor analysis, we identified three categories of hunting habitat; mountain forest, low alpine and high alpine. Mode of hunting is more important than residence status in terms of preferred habitat. Hunters using dogs preferred mountain forest and low alpine habitats more than hunters without dogs. Hunters without dogs had a higher preference than dog hunters for high alpine habitats. Hunters with mixed modes of hunting have wider habitat preferences. Residence status only affects the perception of the mountain forest habitat. The results may have implications for management as land use and place-based meanings are currently changing in many natural and rural landscapes, and hunting needs to be integrated with other recreational uses.